CU-AL-BE VE CU-AL-Nİ ALAŞIMLARININ MEKANİK ETKİLERLE ŞEKİL HATIRLAMA ÖZELLİKLERİNDEKİ DEĞİŞİMLERİNİN İNCELENMESİ - BALO, Ş. NEVİN (Fırat Üniveristesi, 1999)
Bu çalışmada incelenen Cu-1 1.8Al-0.47Be ( ağırlık yüzdeli ) alaşımı austenit fazında D03 yapısına, Cu-ll.6Al-0.42Be, Cu-13.5Al-4Ni, Cu-13A1 4Ni ( ağırlık yüzdeli ) alaşımları austenit fazında DO3, martensit fazındal8R yapılara sahiptirler. Bu alaşımlara uygulanan mekanik zor ve zorlanmaların şekil hatırlama davranışlarına etkileri metalografik metotlar ( optik mikroskobu, taramalı elektron mikroskobu ), x-ışını difraksiyonu ve termal analiz metotları ile incelendi Austenit fazda bulunan Cu-ll.8Al-0.47Be alaşımına T > Af sıcaklığında, martensit fazda bulunan Cu-1 1.6Al-0.42Be alaşımına da T < As sıcaklığında 1 13.6 kg/mm2 lik basma zoru uygulandığında şekil hatırlama özelliklerinin kaybolduğu belirlendi Ayrıca T < As sıcaklığında Cu-13.5Al-4Ni ve Cu-13Al-4Ni alaşımlarında şekil hatırlama özelliklerinin uygulanan çekme zoru ile kaybolmadığı tespit edildi Uygulanan çekme ve basma zorlarına bağlı olarak yeni martensit fazların oluştuğu, mevcut martensitler içinde ikizlenmelerin ve yeni çökelti fazlarının oluştuğu belirlendi. Deformasyon derecesine bağlı olarak örgü parametrelerinde küçük değişimlerin meydana gelmesine rağmen a/b oranının V3/2 den küçük olduğu austenit ve martensit fazların uygulanan zorlardan bozulmadığı belirlendi. Diğer taraftan uygulanan zorların ters dönüşüm sıcaklıklarını yükselttiği tespit edildi. Anahtar Kelimeler: Cu-Al-Be ve Cu-Al-Ni alaşımları, şekil hatırlama olayı, zor-zorlanma, martensitik dönüşüm, dönüşüm sıcaklıkları

In this study, shape memory properties of Cu-ll.8Al-0.47Be, Cu-ll.6Al-0.42Be, Cu-13.5Al-4Ni and Cu-13Al-4Ni alloys have been investigated. Effects of mechanically applied stress on the shape memory behaviour of these alloys were studied by metalographic methods ( optical microscope and scanning electron microscope ), x-ray diffraction and thermal analysis methods. The alloys studied in this work have DO3 structure in the austenite phase and have 18R structure in the martensite phase. But only Cu-ll.8Al-0.47Be alloys was in the austenite phase the other alloys were 18R martensite phase in the room temperature. It was observed that when a compressive stress of 113.6 kg/mm2 is applied to Cu-1 1.8Al-0.47Be alloy at T > Af in austenite phase region and Cu-1 1.6Al-0.42Be alloy at T < As in martensite phase region, the shape memory behaviours disappeared on the other hand, it was found that the shape memory features were not affected if an tensile stress is applied at T < As to the Cu-13.5Al-4Ni and Cu-13Al-4Ni alloys.The new martensites, twinnings, and precipitation phases were formed in the present martensites depending on the applied tensile and compressive stresses. Despite small changes in the lattice parameters with deformations, it was fount that the a/b ratio of martensite structure is less than V3/2 and this ratio was not affected, and austenite-martensite crystal structures were not disturbed by the applied stresses. However, it has been determined that inverse transformation temperatures have a tendency to increase proportional to the applied stresses. Key words: Cu-Al-Be and Cu-AI-Ni alloys, shape memory alloys, stress-strain, martensite transformation, transformation temperatures.
The investigation shape memory properties of Cu-Al-Be and Cu-Al-Ni alloys by mechanical effects
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering